The Cavovarus Foot and It's Association with Fractures of the Fifth Metatarsal. Issue 3 (11th September 2017) - Fuchs, Daniel; Kane, Justin; Brodsky, James; Royer, Christian; Zide, Jacob; Reddy, Veerabhadra; Bhimani, Aamir; Daoud, Yahya
Category: Midfoot/Forefoot, Trauma Introduction/Purpose: Fifth metatarsal fractures are the most commonly encountered metatarsal fractures. It is often inferred that fifth metatarsal fractures occur at an increased frequency in patients with cavovarus foot position. In particular, zone 2 and zone 3 fractures are thought to be associated with cavovarus feet. However, limited data exists in the literature to support this claim. The hypothesis of this study is that a cavovarus foot alignment is positively correlated with the incidence of fifth metatarsal fractures. Methods: 298 consecutive fifth metatarsal fractures were compared with a matched control group of 104 patients presenting to an orthopaedic clinic for toe fractures, interdigital neuromas and plantar fasciitis. Radiographic parameters were measured on weight-bearing anteroposterior and lateral x-rays for all patients. An ANOVA test was utilized to compare radiographic parameters between patients with fifth metatarsal fractures and the control group. Parameters that were found to be statistically significant were further analyzed using a Tukey-Kramer test to compare controls and each type of fifth metatarsal fracture (zone 1, zone 2, zone 3, distal oblique diaphyseal, metatarsal neck). Results: All radiographic parameters are listed in table 1. A statistically significant difference (p<0.05) for calcaneal pitch, lateral talocalcaneal angle, AP talo-2nd metatarsal angle, talonavicular coverage angle and AP talocalcaneal angle were detected. All parameters are indicative of increased cavovarus in the fifth metatarsal fracture group when compared with controls. In the subgroup analysis, zone 1, zone 2, zone 3 and distal oblique diaphyseal fractures each had a calcaneal pitch, lateral talocalcaneal angle and AP talocalcaneal angle consistent with a more cavovarus position than the control group (p<0.05). Zone 2 and zone 3 fractures had an AP talo-2nd metatarsal angle more consistent with cavovarus than zone 1 fractures and controls. For all other parameters there were no significant differences between each type of fifth metatarsal fracture. Conclusion: While it is commonly accepted that cavovarus is a risk factor for fifth metatarsal fractures, there's little evidence in the literature to support this. This study is the first to show that there is a positive correlation between radiographic parameters that reflect cavovarus foot position and the incidence of fifth metatarsal fractures compared to a matched control group of patients with unrelated pathology. Furthermore, while zone 2 and zone 3 fractures are most commonly thought to be associated with cavovarus, each subcategory of fifth metatarsal fractures in this study had radiographic measurements more consistent with cavovarus foot position than controls.